Effect of groundwater flow on a ground heat exchanger - Aresti, Lazaros; Florides, Georgios A.; Christodoulides, Paul; Messaritis, Vassilios (My University, 2016)
Multiple layer underground and the flow of ground water in some layers have an important effect on the heating of vertical heat columns and heat exchangers (HE). This paper investigates the important implication on the design of the Ground HE with regard to their heating effect. For this reason a thermal model is constructed in Comsol Multiphysics software and the effect of various parameters such as thermal conductivity of the ground and the groundwater flow velocity is considered. The model parameters are set to present actual (known) parameters of an installed column and validated against experimental values. Although the key for an overall capital cost reduction is the borehole length, the results indicate that by using the groundwater available, construction of shallow Ground Source Heat Pump systems can be achieved with an increase of the coefficient of performance (COP).
Keywords: Multiple layer underground; Ground water; Heat exchangers